Association between expertise in clinical skills and mental functions networking related to manual dexterity - Chia-Shu Lin; Tzu-I Chen; Cheng-Chieh Yang (BMC Medical Education)
Abstract Background Manual dexterity is key to clinical skill training. The networking between sensorimotor and visual-attention functions may be associated with the expertise of dental students. The study aims to investigate the pattern of networking between sensorimotor and visual-attention functions and related resting-state (rs) functional connectivity (FC). Methods Twenty-six dental and 19 non-dental students completed visual-attention tests and psychomotor tests for manual dexterity and steadiness. Thirty participants also received structural and rs-functional magnetic resonance imaging. Results Compared to non-dental students, dental students showed increased networking in performance between visual-attention tests and manual dexterity, increased rsFC between bilateral sensorimotor network (SMN) and the left middle frontal gyrus, and decreased rsFC between bilateral SMN and the left posterior insula. Better performance of manual dexterity was associated with increased rsFC between the left SMN and the right supramarginal gyrus. Conclusions Dental skill training is associated with the networking of sensorimotor and visual-attention functions and coupled with increased rsFC of the SMN. In dental students, better manual dexterity is associated with the functional connectivity of the SMN. Clinical trial number Not applicable.